(untitled) (Journal of Science and Technology, 2016)
The paper assesses the effects of traditional values (collective conceptions of what is considered good, desirable and proper or bad, undesirable and improper in a given society) and socio-cultural factors (these are models of life, human rights, value systems, customs, beliefs and arts) on human resource management (HRM) in public sector organizations in Ghana and the need for Human Resource (HR) Managers to “rethink their role, to overcome the difficulties inherent in their position”. Socio-cultural practices are the distinctive, spiritual, material, intellectual and emotional features that characterize a society or a social group. Ghanaian worker in general and the HR manager in particular is influenced by socio-cultural practices and values of a larger society of which he/she is a member. For instance, the HR manager is in dilemma as to whether or not to refuse a worker\’s permission to attend funerals, naming ceremonies, festivals or visit relatives at hospital during working hours. In other words, HR manager is at cross-roads as to what to do in order to maintain his/her job while holding on to his/her socio-cultural practices when some of these practices contravene the organizational code of conduct. Among these factors, is how to deal with the traditional values and socio-cultural environment within which (HR) specialists find themselves. The paper therefore focuses on the impact of some of the traditional values such as the pressure from family members, attitudes and socio-cultural factors. The purposive sampling technique was used to select the directors and the simple random sampling method was used to select the other respondents. Questionnaires were designed and self-administered questionnaire and face -to-face interview methods were used to obtain information for the study. Thus, the traditional values and socio-cultural factors, which the society maintains, remain strong among workers and have impacted on the work of HR specialist in spite of the conflicting values prescribed by the public sector organizations.